Media ethics : cases and moral reasoning - Christians, Clifford G.; Fackler, Mark; Kreshel, Peggy J. (Peggy Jean), 1953-; Brown, William J. (Professor of communication); Feng, Yayu; Overton, Holly K.; McKee, Kathy Brittain (New York: Routledge, 2025)
"Through original case studies and analyses of real-life media experiences, Media Ethics challenges readers to think analytically and critically about ethical situations in mediated communication. This textbook provides a comprehensive introduction to the theoretical principles of ethical philosophies, facilitating awareness and critical reflection of ethical issues. In each chapter, the authors examine case studies spanning several continents and geopolitical and cultural contexts. To provide a framework for analyzing the cases and exploring the steps in moral reasoning, the book introduces the Potter Box, a powerful tool for moral analysis. Focusing on a wide range of ethical issues faced by media practitioners and news organizations, the cases in this new twelfth edition include the most prominent concerns in journalism, broadcasting, advertising, public relations, and entertainment today. It explores new topics such as the use of ChatGPT in newsrooms, the privacy implications of biometric technologies, the role of public relations in political campaigns, and advertisers' approach to sustainability and climate change. This core textbook is ideal for classes in media and communication ethics, journalism, public relations, advertising, entertainment media, and popular culture. Online Instructor and Student Resources including video introductions to each chapter, PowerPoint slides, sample discussion and exam questions and links to further resources are available at www.routledgelearning.com/mediaethics"--
Includes bibliographical references and index.
Keywords: Mass media -- Moral and ethical aspects